POLYMERIZATION OF EUGENOL USING A CONCENTRATED NITRIC ACID (HNO3) CATALYST AND MEDIA OF ACETIC ACID (CH3COOH) - Denliana H.N. Pakaya; Paulus Hengky Abram (Media Eksakta, 2020)
Eugenol is a paleyellow oily liquid which can be extracted from essential oils such as clove and cinnamon oils. This study aimed to modify eugenol and to reduce environmental pollution caused by polymers by utilizing natural materials through polymerization of eugenol with concentrated nitric acid (HNO3) and media of acetic acid (CH3COOH). Various of acetic acid media used were 5%, 25%, and 50%. The result of polieugenol was blackish brown, in the form of shiny gels, smelling of cloves, and soluble in ethanol, slightly soluble in chloroform and insoluble in benzene and water. The product polieugenol was washed with aquades. The yields before washing were 142.75%, 141.25% and 138.75%, and the yield after washing were 88.265%, 88.397% and 87.248%. The Fourier Transform InfraRed (FT-IR) spectrophotometer results showed that the polymerization did not occur perfectly showing by absorption peaks of CH=CH2 and C = C groups at 995.27 and 1635.89 cm-1.